Delusional versus nondelusional body dysmorphic disorder: Clinical features and course of illness - Phillips, K.A. (2005)
DSM-IV’s classification of body dysmorphic disorder (BDD) is controversial. Whereas BDD is classified as a somatoform disorder, its delusional variant is classified as a psychotic disorder. However, the relationship between these BDD variants has received little investigation. In this study, we compared BDD’s delusional and nondelusional variants in 191 subjects using reliable and valid measures that assessed a variety of domains. Subjects with delusional BDD were similar to those with nondelusional BDD in terms of most variables, including most demographic features, BDD characteristics, most measures of functional impairment and quality of life, comorbidity, and family history. Delusional and nondelusional subjects also had a similar probability of remitting from BDD over 1 year of prospective follow-up. However, delusional subjects had significantly lower educational attainment, were more likely to have attempted suicide, had poorer social functioning on several measures, were more likely to have drug abuse or dependence, were less likely to currently be receiving mental health treatment, and had more severe BDD symptoms. However, when controlling for BDD symptom severity, the two groups differed only in terms of educational attainment. These findings indicate that BDD’s delusional and nondelusional forms have many more similarities than differences, although on several measures delusional subjects evidenced greater morbidity, which appeared accounted for by their more severe BDD symptoms. Thus, these findings offer some support for the hypothesis that these two BDD variants may constitute the same disorder. Additional studies are needed to examine this issue, which may have relevance for other disorders with both delusional and nondelusional variants in DSM.